Fast detection and quantification of four dairy propionic acid bacteria in milk samples using real-time quantitative polymerase chain reaction. (October 2016) - Turgay, Meral; Schaeren, Walter; Wechsler, Daniel; Bütikofer, Ueli; Graber, Hans Ulrich
Abstract: Propionibacterium freudenreichii is added to vat milk to create the characteristic eyes and typical nutty flavour of Emmentaler Protected Designation of Origin (PDO) cheese, but leads to serious quality defects in other raw milk cheeses from Switzerland. To trace propionic acid bacteria (PAB) in raw milk, we developed and validated a fast quantitative polymerase chain reaction (qPCR)-based method for P. freudenreichii, Propionibacterium thoenii, Propionibacterium jensenii, and Propionibacterium acidipropionici . qPCR-standard curves were linear over five log units down to 10 1 copies per reaction (R ≥ 0.997); efficiencies ranged from 0.83 to 0.97. In spiking experiments, the lower limits of quantification were 10 1 –10 2 cfu mL −1 raw milk. Fifty one vat milk samples were analysed with plate count method and qPCR in parallel. Compared with the classic plate count method, the newly developed qPCR method gave faster and species specific determination of four dairy PAB in milk and yielded comparable quantitative results.